Predictors of cardiac neuromodulation achieved by cryoballoon ablation performed in patients with atrial fibrillation who were in sinus rhythm before the ablation. (1st July 2020) - Maj, Riccardo; Borio, Gianluca; Osório, Thiago Guimarães; Iacopino, Saverio; Ströker, Erwin; Sieira, Juan; Terasawa, Muryo; Rizzo, Alessandro; Galli, Alessio; Varnavas, Varnavas; Bala, Gazim Gezim; Paparella, Gaetano; et al.
Abstract: Background: The impact of pulmonary vein isolation (PVI) performed with cryoballoon (CB) on the intrinsic cardiac autonomic nervous system (ICANS) remains unclear. Objective: The purpose of this study was to evaluate the predictors and the clinical meaning of cardiac neuromodulation achieved by CB-ablation as assessed by sinus heart rate (HR) response after the procedure. Methods: Patients who underwent CB-ablation for drug-resistant atrial fibrillation (AF) from January 2014 to October 2018 were included. Twelve‑leads rest ECG was taken both before and after the procedure. After discharge, patients were scheduled for follow-up visits at 1, 3, 6, and 12 months and 24 h Holter recordings were obtained at each follow-up visit. All documented AF episodes of >30 s were considered as recurrence. Results: Four-hundred seventy-two patients (62.3% male, age 56.7 ± 13.6 years, 97.2% paroxysmal AF) were included. Mean HR before the procedure was 60.17 ± 10.4 bpm, while the morning after the procedure mean HR was 75.48 ± 12.0 bpm. Age at enrollment (R = −0.26; p < 0.001), baseline HR before the CB-A (R = −0.32; p < 0.001), nadir temperature in each right pulmonary vein (R = −0.11, p = 0.022; R = −0.16; p = 0.001) were significantly associated with the ∆HR. At 2-year follow-up, freedom from recurrences was 83.1% for the patients with HR increase ≥15 bpm after CB-A and 66.3% in patients with HR increase ˂15 bpm (p = 0.021). Conclusion: Sinus HR increase is a frequent phenomenon after CB-A, that can be predicted by both clinical and procedural factors and that correlates with better outcome after cryo-PVI. Highlights: Cryoballoon ablation may have a role on intrinsic cardiac autonomic nervous system. Vagal denervation with cryoballoon ablation may contribute to the clinical outcome. Clinical and procedural factors can predict heart rate increase after the procedure. Significant heart rate increase is associated with fewer arrhythmic recurrences.